Short-Wavelength and Infrared Autofluorescence Imaging in Pachychoroid Neovasculopathy - Norihiko Nakagawa; Takuya Shunto; Issei Nishiyama; Kohei Maruyama; Miki Sawa (Vision)
Purpose: The purpose of this paper is to investigate the relationship between short-wavelength autofluorescence (SWAF) and infrared autofluorescence (IRAF) patterns in pachychoroid neovasculopathy (PNV) with serous retinal detachment (SRD). Methods: This study used an observational case series of 62 eyes of 58 consecutive patients diagnosed with symptomatic PNV from January 2019 and October 2021 at a single institution. SWAF and IRAF patterns were analyzed with disease chronicity, and autofluorescence changes in macular neovascularization (MNV) were assessed in two images. Results: SWAF patterns and the mean duration of symptoms were as follows: blocked (15 eyes, 24%), 1.0 months; mottled (8 eyes, 13%), 2.8 months; hyper (24 eyes, 39%), 5.0 months; hyper/hypo (10 eyes, 16%), 7.0 months; descending tract (5 eyes, 8%), 12.0 months (p < 0.01). IRAF patterns and the mean duration of symptoms were as follows: blocked (17 eyes, 27%), 1.0 months; hyper (22 eyes, 35%), 4.0 months; mixed/hyper dominant (9 eyes, 15%), 5.0 months; mixed/hypo dominant (9 eyes, 15%), 6.8 months; descending tract (5 eyes, 8%), 12.0 months (p < 0.01). Abnormal autofluorescence corresponding to MNV lesion was seen in 34 eyes (55%) with SWAF and 59 eyes (95%) with IRAF (p < 0.01). Conclusions: SWAF and IRAF show multiple patterns and are related to disease chronicity in symptomatic PNV. IRAF could be helpful in detecting the lesion of MNV.